Evaluating the thermal behavior and structural integrity of potato cold storage facilities: insights for design optimization - Yilmaz, Ismail Cengiz; Yilmaz, Deniz; Mancuhan, Ebru; Ince, Ibrahim Timucin (Frontiers in Sustainable Food Systems, 2025)
This study examines the impact of thermal loading on the structural integrity of two types of potato storage facility: naturally cooled underground warehouses and steel-constructed refrigerated warehouses. Cold storage facilities are widely used for long-term storage of agricultural produce such as potatoes under varying indoor/outdoor temperature conditions. The finite element method (FEM) using SAP2000® was employed to model and evaluate the structural responses of these storage systems to thermal loading. The research focuses on the deformation, displacement and bending moments experienced by these structures. The findings reveal significant differences in the durability and performance of the two storage types. These results highlight important considerations for their design and structural optimisation. Based on these insights, recommendations are proposed to enhance the efficiency and longevity of cold storage facilities. This study contributes to the existing body of knowledge on the thermal behavior of storage infrastructures, offering valuable guidance on improving the design and operational effectiveness of agricultural cold storage systems.